Hydrodynamic Effects of Tidal-Stream Power Extraction for Varying Turbine Operating Conditions - Lilia Flores Mateos; Michael Hartnett (Energies, 2020)
Realistic evaluation of tidal-stream power extraction effects on local hydrodynamics requires the inclusion of the turbine’s operating conditions (TOC). An alternative approach for simulating the turbine’s array energy capture at a regional scale, momentum sink-TOC, is used to assess the impact of power extraction. The method computes a non-constant thrust force calculated based on the turbine’s operating conditions, and it uses the wake induction factor and blockage ratio to characterise the performance of a turbine. Additionally, the momentum sink-TOC relates the changes produced by power extraction, on the velocity and sea surface within the turbine’s near-field extension, to the turbine’s thrust force. The method was implemented in two hydrodynamic models that solved gradually varying flows (GVF) and rapidly varying flows (RVF). The local hydrodynamic effects produced by tidal-stream power extraction for varying the turbine’s operating conditions was investigated in (i) the thrust and power coefficient calculation, (ii) flow rate reduction, and (iii) tidal currents’ velocity and elevation profiles. Finally, for a turbine array that operates at optimal conditions, the potential energy resource was assessed. The maximisation of power extraction for electrical generation requires the use of an optimum turbine wake induction factor and an adequate blockage ratio, so that the power loss due to turbine wake mixing is reduced. On the other hand, the situations where limiting values of these parameters are used should be avoided as they lead to negligible power available. In terms of hydrodynamical models, an RVF solver provided a more accurate evaluation of the turbine’s operating conditions effect on local hydrodynamics. Particularly satisfactory results were obtained for a partial-fence. In the case of a fence configuration, the GVF solver was found to be a computationally economical tool to pre-assess the resource; however, caution should be taken as the solver did not accurately approximate the velocity decrease produced by energy extraction.